Anxiety and quality of life among nursing students undergoing clinical placement during COVID-19 pandemic - Wira, Wan Muhammad Najmi Taufiq Wan (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
This study will concentrate on nursing students' Quality of Life and anxiety during clinical placement during the COVID-19 pandemic. In this study, nursing students who were placed in clinical settings during the COVID-19 pandemic were asked about their levels of anxiety and quality of life. In addition, this study explores the relationship between anxiety and nursing students' quality of life during clinical placement as well as the association between sociodemographic data and the students' anxiety levels during the COVID-19 pandemic. From March 2022 to May 2022, data were gathered online using a series of questions that were modified from Firdaus Mukhtar & Nor Sheereen Zulkefly (2011) and Hasanah et al. (2003). Through simple random sampling, 169 nursing took part in the study. This study included nursing students who were enrolled in diploma and degree programmes and ranged in age from 19 to 29. The results showed that the majority of USM nursing students (n = 53, 31.4%) reported low levels of anxiety. The results for quality of life showed that it was less than average for nursing students, with mean values for the different quality of life domains being as follows: physical health = 65.54 (SD = 18.71), psychological = 22.25 (SD = 3.97), social relationship = 39.05 (SD = 14.14), and environmental = 74.88 (SD = 15.92). For all domains, there was a statistically significant difference between the amount of anxiety and the level of life quality (p=0.001). One sociodemographic factor, race, has a statistically significant relationship with anxiety level (p=0.001). In conclusion, the findings also revealed low levels of quality of life, indicating that even if the amount of anxiety was small, the quality of life for nursing students at USM may still be raised. Therefore, increasing welfare and education capabilities can be thought of as enhancing life quality.